Online social networking and work-family balance: friends or foes? - Farivar, Farveh (Curtin University, 2015)
To date, the majority of research in relation to online social networking (OSN) has focused on its separate influences on either the family domain or the workplace domain. This study brings together the elements of family satisfaction and work satisfaction to explore whether OSN increases the conflict between work and family domains. Analysing the data from a web-based survey distributed across Australia (n=379) suggested OSN is a predictor of work-family conflict.